Ultrasonographic Mapping of the Location and Depth of Labial Arteries Prior to Lip Augmentation: A Pilot Study - , Débora de Freitas Brasil; , Letícia Sales Leite Ramalho Lima; , Lívia dos Santos Fornagero; , José Evando da Silva Filho; , Bruno Frota Amora Silva; , Danielle Frota de Albuquerque (Archives of Current Research International, 2024)
Aims: This study aims to map the superior and inferior labial arteries in terms of their anatomical location and depth using ultrasound imaging to optimise the planning of lip augmentation procedures in a Brazilian cohort. Study Design: Observational cross-sectional pilot study. Place and Duration of Study: The examinations were conducted at the dental clinic of the University of Fortaleza during October-November 2023. Methodology: Nineteen volunteers (both sexes, aged 18 to 55 years) with no history of previous lip augmentation participated in this study. Imaging was performed using a high-frequency ultrasound machine (Evus 5, Alliage S/A), equipped with a 7–14 MHz linear transducer, in both B-mode and Doppler modes. Statistical analyses included the Shapiro-Wilk test, Levene's test, analysis of variance (ANOVA), T-test, Pearson's correlation coefficient, standard deviation, confidence intervals, and Fisher's exact test, all conducted using Python software. Results: The superior labial artery was predominantly located in the intramuscular region in 68.42% of cases, followed by the submucosa in 31.58%, with no instances in the subcutaneous layer. For the inferior labial artery, a similar distribution was observed: 63.16% intramuscular, 31.58% submucosal, and 5.26% subcutaneous. Statistically significant differences (p < 0.05) were identified in the depth and location of the labial arteries based on sex and specific anatomical regions. Conclusion: This study demonstrates the variation in the depth and location of labial arteries, with a significant predominance in the intramuscular layer. Ultrasound serves as an essential tool for mapping vascular anatomy in the planning of lip augmentation, underscoring the value of thorough anatomical assessment to enhance procedural safety and efficacy.